Phased-Array Transducer for Intracardiac Echocardiography Based on 1–3 Piezocomposite - Han, Zhile; Wang, Ninghao; Li, Zhangjian; Zhu, Xinle; Chen, Youwei; Jian, Xiaohua; Cui, Yaoyao (Frontiers in Materials, 2021)
An ultrasonic phased array transducer was proposed in this paper, which could effectively improve the imaging performance by using 1-3 piezocomposite. The piezocomposite consists of PZT and epoxy, with a pitch of 70 μm, kerf of 20 μm, and thickness of 170 μm. The phased array transducer has 64 elements, each element is in the size of 85 μm × 1.3 mm, the pitch of the transducer is 100 μm, and the kerf between the elements is only 15 μm. To minimize the transducer size, the 1-3 composite uses an encase structure, which connects the upper surface of the composite directly to the flexible circuit board bonded to the lower surface as the ground electrode. The final fabricated transducer is in the size of 2 mm × 7.4 mm and mounted in a 9 F (3 mm diameter) catheter, which can bend in four directions and is primarily used for intracardiac echocardiography. The acoustic and electrical properties of the transducer were tested, including impedance, echo sensitivity, center frequency (9 MHz), bandwidth (55%), consistency, etc. At last, wire phantom experiments were carried out to demonstrate the spatial resolutions and imaging performance. The study shows that this transducer with compact design and construction can bring higher performance for the single-use disposable ICE catheter.